A Study on Generation Z Preference for Quick Delivery Grocery Products on Big Basket in Ahmedabad City - Romil Vyas; Ankit Vataliya; Jignesh Vidani (MultiTech Publisher, 2024)
The aim of this study is to look at Generation Z preferences over fast delivery grocery services on Big Basket in Ahmedabad city. Because online grocery shopping has increased, e-commerce needs to focus more on understanding the younger generation consumer behavior, particularly Gen Z. In the given paper, the influencing factors over decision-making by Gen Z users were considered along with focusing areas such as speed, experience offered to customers, cost, product quality, and sustainability. Data was collected through a survey administered to a sample of Generation Z consumers in Ahmedabad, with key findings that speed and convenience are paramount over cost considerations. Further, the study underlines the user-friendly mobile applications and the importance of product quality and availability in shaping consumer satisfaction. It also reveals a growing awareness about sustainability concerns, which leads to the conclusion that Generation Z values environmentally conscious practices. The study's findings are also pragmatic in their application to an online grocery marketplace like Big Basket, implying a need for speed of delivery, improvement in technology-related features, and sustainability integration in terms of practice so that such platforms cater better to this type of target audience. On a theoretical plane, the study further contributes to existing literature regarding consumer behavior, adoption of technology, and generational preferences in terms of online grocery shopping. Overall, the study provides an exhaustive understanding of Generation Z's online grocery shopping habits and serves as a base for future research in this area